18F-FDG PET/CT Imaging of the Pancreas: Spectrum of Diseases - Nguyen, Vien X; Nguyen, Cuong C; Nguyen, Ba D (JOP. Journal of the Pancreas, 2011)
Since the introduction of integrated positron emission tomography-computed tomography (PET/CT), it has a great impact on the field of oncology. Comparing to other conventional scanners, only PET/CT is capable of providing important information on accurate detecting, staging/restaging, and post-therapeutic monitoring of many cancers. Many studies have demonstrated that PET/CT changes the management in approximately 30% of all cancer patients. Because 2-(18F)-fluoro-2-deoxy-D-glucose (FDG) is a nonspecific tracer, understanding the PET/CT limitations and pitfalls for various pancreatic conditions can lead to more accurate interpretation of PET/CT images, which ultimately would impact patient care. As a result, it is important for radiologists and other clinicians to familiarize themselves with a wide spectrum of pancreatic PET/CT findings simulating cancer from benign entities. <!–[if gte mso 9]> Normal 0 14 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>